2004
DOI: 10.1080/00498250412331285463
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of human cytochrome P450 marker substrates in mouse: a strain and gender comparison

Abstract: The aim was to characterize mouse gender and strain differences in the metabolism of commonly used human cytochrome (CYP) P450 probe substrates. Thirteen human CYP probe substrates (phenacetin, coumarin, 7-ethoxy-4-trifluoromethyl coumarin, amiodarone, paclitaxel, diclofenac, S-mephenytoin, bufuralol, dextromethorphan, chlorzoxazone, p-nitrophenol, testosterone and lauric acid) were used in activity measurements. The metabolism of the probe substrates was compared in liver microsomes from male and female NMRI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 25 publications
1
29
1
Order By: Relevance
“…However, Cyp2d22 is known to be highly expressed in both male and female mouse liver and is modestly expressed in a variety of other tissues, such as adrenal, ovary, and mammary glands (Blume et al, 2000). Thus, our results would suggest that Cyp2d22 is not the CYP2D isozyme responsible for the CYP2D6-like enzyme activity reported by Lofgren et al (2004) in female mouse liver.…”
Section: Discussioncontrasting
confidence: 37%
See 2 more Smart Citations
“…However, Cyp2d22 is known to be highly expressed in both male and female mouse liver and is modestly expressed in a variety of other tissues, such as adrenal, ovary, and mammary glands (Blume et al, 2000). Thus, our results would suggest that Cyp2d22 is not the CYP2D isozyme responsible for the CYP2D6-like enzyme activity reported by Lofgren et al (2004) in female mouse liver.…”
Section: Discussioncontrasting
confidence: 37%
“…Given the sequence similarity with CYP2D6, we reasoned that characterization of the enzymatic function for the encoded Cyp2d22 protein would contribute to the understanding of the CYP2D6-like phenotype or lack thereof in mice. Recently, Lofgren et al (2004) reported CYP2D6-like enzymatic activity in mouse liver microsomes. This activity correlated with a protein that was immunoreactive to anti-rat Cyp2d4 antibody and that appeared more prevalent in females than males (Lofgren et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a whole, our data are suggestive of breed differences in DME expression in cattle, likewise to laboratory species (Casley et al, 1997;Jang et al, 2001;Löfgren et al, 2004;Saito et al, 2004;Stott et al, 2004). Differences in DME expression are likely to influence both the bioavailability and clinical efficacy of xenobiotics (Sallovitz et al, 2002), and these same might be of particular concern in farm animals, for the hypothetical presence of potentially harmful residues in foodstuffs of animal origin.…”
Section: Effect Of Breed Upon Drug-metabolizing Enzymes In Cattlementioning
confidence: 82%
“…Dextromethorphan is metabolized to dextrorphan by CYP2D mainly in mouse, rat, dog, monkey and pig liver as well as in human liver [14,21,26,55,56]. Therefore we used dextromethorphan and its major metabolite, dextrorphan, is often used as probe drugs to evaluate the activity of the CYP2D isoform.…”
Section: Discussionmentioning
confidence: 99%